Determinants of safer-sex behaviors of brothel female commercial sex workers in Jakarta, Indonesia - Sedyaningsih-Mamahit, Endang R.; Gortmaker, Steven L. (The Journal of sex research, 1999)
A cross-sectional survey was conducted in Kramat Tunggak, an official brothel complex in Northern Jakarta. The objectives were to investigate factors that influence the female commercial sex workers' consistent practice of condom use. These factors were classified into personal behaviors and external factors, such as government programs and the brothel managers' and the clients' attitudes towards condom use. After controlling for sociodemographic factors, the sexworkers' previous experiences in negotiating condom use and in using them for family-planning purposes were found to be significantly directly associated with consistent condom use. On the other hand, the clients' and the brothel managers' attitudinal barriers towards condom use and the sexworkers' exposure to government programs were inversely associated with consistent condom use. Changes in the government STD/AIDS-related policy, education, and health programs among the female sex-worker community is urgently needed to substantially increase their condom use practice.